Respuesta :
The general equation of a circle is given by;
[tex] (x-a)^{2}+ (y-b)^{2} = r^{2} [/tex]
Where (a, b) is the centre of the circle and r is the radius.
For the given circle, centre is (0,0) and r=11
[tex] (x-0)^{2} + (y-0)^{2} = 11^{2} [/tex]
[tex] x^{2} + y^{2} = 11^{2} [/tex]
[tex] (x-a)^{2}+ (y-b)^{2} = r^{2} [/tex]
Where (a, b) is the centre of the circle and r is the radius.
For the given circle, centre is (0,0) and r=11
[tex] (x-0)^{2} + (y-0)^{2} = 11^{2} [/tex]
[tex] x^{2} + y^{2} = 11^{2} [/tex]
The general equation of a circle is expressed as:
(x-a)^2+ (y-b)^2 = r^2
Where the point (a, b) is the center of the circle and r is the radius.
For the given circle, center is (0,0) and r=11
Therefore, the equation of the circle would be:
(x)^2+ (y)^2 = 11^2
(x)^2+ (y)^2 = 121
(x-a)^2+ (y-b)^2 = r^2
Where the point (a, b) is the center of the circle and r is the radius.
For the given circle, center is (0,0) and r=11
Therefore, the equation of the circle would be:
(x)^2+ (y)^2 = 11^2
(x)^2+ (y)^2 = 121